The synthesis and coupling of photoreactive collagen-based peptides to restore integrin reactivity to an inert substrate, chemically-crosslinked collagen. (April 2016) - Malcor, Jean-Daniel; Bax, Daniel; Hamaia, Samir W.; Davidenko, Natalia; Best, Serena M.; Cameron, Ruth E.; Farndale, Richard W.; Bihan, Dominique
Abstract: Collagen is frequently advocated as a scaffold for use in regenerative medicine. Increasing the mechanical stability of a collagen scaffold is widely achieved by cross-linking using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS). However, this treatment consumes the carboxylate-containing amino acid sidechains that are crucial for recognition by the cell-surface integrins, abolishing cell adhesion. Here, we restore cell reactivity to a cross-linked type I collagen film by covalently linking synthetic triple-helical peptides (THPs), mimicking the structure of collagen. These THPs are ligands containing an active cell-recognition motif, GFOGER, a high-affinity binding site for the collagen-binding integrins. We end-stapled peptide strands containing GFOGER by coupling a short diglutamate-containing peptide to their N-terminus, improving the thermal stability of the resulting THP. A photoreactive Diazirine group was grafted onto the end-stapled THP to allow covalent linkage to the collagen film upon UV activation. Such GFOGER-derivatized collagen films showed restored affinity for the ligand-binding I domain of integrin α2 β1, and increased integrin-dependent cell attachment and spreading of HT1080 and Rugli cell lines, expressing integrins α2 β1 and α1 β1, respectively. The method we describe has wide application, beyond collagen films or scaffolds, since the photoreactive diazirine will react with many organic carbon skeletons.